1993
DOI: 10.1117/12.161977
|View full text |Cite
|
Sign up to set email alerts
|

<title>Thermal and chemical metallic-dielectric transitions of TiNxOy-Cu absorber tandems</title>

Abstract: Reliability and structural properties of selective TiNO-Cu tandem absorbers for solar applications at high temperatures were investigated. A tempering process which improves thermal emittance of the coatings was observed. Degradation is monitored by directional total thermal emittance. Four steps of degradation have been separated and confirmed by XRD, EDAX, REM and optical spectroscopy. Coatings show crystalline phases and transitions to amorphous due to degradation and tempering. They are susceptible to oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…This destroys the selective properties and mechanical stability of the film. The final fourth step is the reconstruction of a chemically stable amorphous film of titanium oxides and crystalline copper oxides with 1-µm craters located at previous pore sites [106]. However, the formation of copper oxide is operative only at elevated temperatures; in the operational range of 350°C, the outer surface is nitrogen rich, not oxygen rich, contrary to the previous literature, and Ti ions are progressively replaced by Cu diffusing from the substrate [107].…”
Section: 1b31mentioning
confidence: 95%
See 1 more Smart Citation
“…This destroys the selective properties and mechanical stability of the film. The final fourth step is the reconstruction of a chemically stable amorphous film of titanium oxides and crystalline copper oxides with 1-µm craters located at previous pore sites [106]. However, the formation of copper oxide is operative only at elevated temperatures; in the operational range of 350°C, the outer surface is nitrogen rich, not oxygen rich, contrary to the previous literature, and Ti ions are progressively replaced by Cu diffusing from the substrate [107].…”
Section: 1b31mentioning
confidence: 95%
“…[104,105]. These coatings are stable in high vacuum, but degrade (mainly the emittance) quickly when exposed to air, of even low partial pressure, at elevated temperatures [106]. After examination of the degradation mechanisms, improvements have been made in the α/ε(100°C)=0.94/0.08-0.12 by replacing the Cu with Al and adding an SiO 2 AR layer, but the construction still needs to be optimized [105].…”
Section: 1b31mentioning
confidence: 99%
“…Different types of SSA, such as metal-dielectric composite, multilayer absorbers and semiconductor-metal tandems have been developed due to their higher thermal absorbance, higher thermal stability and low IR emittance [3][4][5][6]. In recent years, many types of selective solar absorber coatings for mid-to-high-temperature applications were studied, but only a few of them have been successfully commercialized.…”
Section: Introductionmentioning
confidence: 99%
“…This is because N is replaced by O in TiNxOy due to the high reactivity between Ti and O atoms. When the annealing temperature is larger than 450 C, the TiNxOy thin film becomes unstable even in a low pressure atmosphere, and the detailed degradation process has been reported by H. Schellinger [130]. To reduce the convective loss, the heat collecting tube is normally encapsulated in a glass tube, and the chamber between the two tubes is vacuumed [131].…”
Section: Tinxoy Thin Film Based Ssamentioning
confidence: 99%
“…As the absorbing layer in the SSA, TiNxOy thin film has a lot of advantages, such as extraordinary optical properties, high hardness, good chemical and thermal stability, and environmental friendliness [130,126,24]. Furthermore, the absorption property of TiNxOy can be tuned by changing the N/O atomic ratio [134,177]; for example, it was reported that the optical properties of the TiNxOy films fabricated by reactive mid-frequency magnetron sputtering from TiN target can be controlled in terms of the reactive gas flow rate [24].…”
Section: Chapter 4 Design and Modeling Of Tin X O Y Thin Film Based Smentioning
confidence: 99%